2007
DOI: 10.1111/j.1463-1326.2007.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Eplerenone improves prognosis in postmyocardial infarction diabetic patients with heart failure: results from EPHESUS

Abstract: Eplerenone treatment may reduce adverse CV events in diabetic patients with LVSD and signs of CHF following AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 23 publications
2
42
0
2
Order By: Relevance
“…26 Aldosterone induces fibrosis in the heart, blood vessels, and kidney, 25 and the antagonism of mineralocorticoid receptors has been associated with reduced fibrosis in human myocardium, limited ventricular remodeling, and improved survival in patients with ventricular dysfunction and heart failure. 14,[25][26][27][28] Our results suggest a greater benefit in terms of survival if MRA treatment is started as early as possible. a Users who initiated mineralocorticoid receptor antagonists at discharge; b users who filled an mineralocorticoid receptor antagonists prescription 30 to 90 days after discharge; c rates of cardiac medication use up to the matched time of first mineralocorticoid receptor antagonists prescription.…”
Section: Pathophysiological Effects Of Aldosterone and "Aldosterone Ementioning
confidence: 61%
“…26 Aldosterone induces fibrosis in the heart, blood vessels, and kidney, 25 and the antagonism of mineralocorticoid receptors has been associated with reduced fibrosis in human myocardium, limited ventricular remodeling, and improved survival in patients with ventricular dysfunction and heart failure. 14,[25][26][27][28] Our results suggest a greater benefit in terms of survival if MRA treatment is started as early as possible. a Users who initiated mineralocorticoid receptor antagonists at discharge; b users who filled an mineralocorticoid receptor antagonists prescription 30 to 90 days after discharge; c rates of cardiac medication use up to the matched time of first mineralocorticoid receptor antagonists prescription.…”
Section: Pathophysiological Effects Of Aldosterone and "Aldosterone Ementioning
confidence: 61%
“…In these trials 32% of patients were diabetic, highlighting a potential benefit of MR antagonist use to minimise cardiovascular complications in diabetic patients in addition to anti-hyperglycaemic treatment. Subgroup analysis of EPHESUS showed the beneficial effects of eplerenone were also found in patients with diabetes (O'Keefe et al 2008). Diabetic patients treated with eplerenone had a higher rate of absolute risk reduction, compared with patients without diabetes, for both end-point of death from cardiovascular causes or hospitalization for cardiovascular events (5.1 vs. 3.5%).…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 93%
“…The same group has also shown that MR antagonism in vivo and in vitro can lead to browning of white adipocytes demonstrated by increased UCP-1 expression (Armani et al 2014). Eplerenone Eplerenone, a more selective MR antagonist, also benefits patients with heart failure and interestingly has additional benefits in those with diabetes following myocardial infarction compared with those without diabetes (O'Keefe et al 2008). A substudy of the EMPHASIS trial examined diabetes risk, and found no difference in the incidence of type 2 diabetes in heart failure patients with or without eplerenone treatment (Preiss et al 2012).…”
Section: Spironolactone and Eplerenonementioning
confidence: 99%